Neuromuscular Adaptation of Athletes to Variable Training Load Regimes - Prymak, Illia (Педагогічна Академія: наукові записки, 2025)
The relevance of this study is determined by the need for scientific justification of the mechanisms underlying neuromuscular adaptation in athletes in the context of increasing training intensity, greater workload volume and density, and higher demands on functional readiness. Variability in training regimes is considered a key factor in improving the efficiency of neuromuscular regulation, preventing adaptive plateaus, and developing stable motor skills, which is particularly important in personalised sports training. The aim of the article is to identify the physiological and biomechanical regularities of athletes’ neuromuscular adaptation to variable training loads and to provide a scientific rationale for improving the efficiency of this process, taking into account individual patterns of physiological response. Methodology. The research was based on the analysis and synthesis of contemporary scientific literature, physiological and biomechanical data, and elements of pedagogical modelling, which made it possible to examine the nature of changes in electromyographic indicators, the dynamics of functional parameters of the neuromuscular system, and to determine the relationship between workload characteristics and the rate of adaptive responses. Results. The findings demonstrate that the effectiveness of neuromuscular adaptation is ensured through a combination of isotonic, isometric, variable-dynamic, plyometric, and combined training regimes that maintain an optimal balance between stimulation and recovery. A phased dynamic of adaptive responses was identified: from central motor neuron activation and improved intermuscular coordination to the stabilisation of electromyographic parameters and optimisation of motor programmes. It was also revealed that excessive intensity, monotonous loading, and insufficient recovery lead to central and peripheral fatigue, sensorimotor maladaptation, and impaired intermuscular coordination. Conclusions. It has been proven that the individualisation of training based on neuromuscular indicators enhances the development of strength and coordination abilities, reduces the risk of overtraining and injury, and ensures stability in athletes’ functional readiness. Prospects for further research include the development of digital models for predicting adaptive responses, the expansion of practical applications of biofeedback systems, and the study of cognitive and neuropsychological factors influencing the dynamics of neuromuscular adaptation in athletes of various specialisations.